Current Opinions on Etiopathogenesis, Clinical Picture, Diagnosis and Treatment of Irritable Bowel Syndrome - Halimovna, Rasulova Saodat (European Journal of Life Safety and Stability (2660-9630), 2022)
Irritable bowel syndrome is a serious and underappreciated problem in childhood. This topic is not so well studied in pediatrics compared to adult practice, and pediatricians often make this diagnosis to young children without proper justification. The lecture analyzes current opinions on the etiopathogenesis, clinical picture, diagnosis and treatment of irritable bowel syndrome in children. The emphasis is placed on a set of diagnostic criteria that allow us to assume and then confirm the diagnosis. Keywords: functional bowel disorders, irritable bowel syndrome, children, biopsychosocial model, dioctahedralsmectite, polyethylene glycol.